Extracellular Electrophysiological Measurements of Cooperative Signals in Astrocytes Populations - Mestre, Ana L. G.; Inácio, Pedro M. C.; Elamine, Youssef; Asgarifar, Sanaz; Lourenço, Ana S.; Cristiano, Maria L. S.; Aguiar, Paulo; Medeiros, Maria C. R.; Araújo, Inês M.; Ventura, João; Gomes, Henrique L. (Frontiers in Neural Circuits, 2017)
Astrocytes are neural cells that exhibit functional electrical properties sensitive to neuronal activity and capable of modulating neurotransmission. Thus, electrophysiological recordings of astroglial activity are very attractive to study the dynamics of glial signaling. This contribution reports on the use of ultra-sensitive planar electrodes combined with low noise and low frequency amplifiers that enable the detection of extracellular signals produced by primary cultures of astrocytes isolated from rat cerebral cortex. Recorded activity is characterized by spontaneous bursts comprised of discrete signals with pronounced changes on the spike rate and amplitude. Weak and sporadic signals become synchronized and evolve with time to higher amplitude signals with a quasi-periodic behavior, revealing a cooperative signaling mechanism. The methodology presented herewith enables the study of ionic fluctuations of population of cells, complementing the single cells observation by calcium imaging as well as by patch-clamp techniques.